2018
DOI: 10.3168/jds.2018-15057
|View full text |Cite|
|
Sign up to set email alerts
|

Short communication: Teat-end shape and udder-level milking characteristics and their associations with machine milking-induced changes in teat tissue condition

Abstract: Machine milking-induced changes in teat tissue condition, such as congestion and edema, have been associated with teat canal openness, penetrability, and thus susceptibility to new intramammary infections and diminished animal well-being. The primary objective of this study was to investigate the association of teat-end shape and machine milking-induced shortterm changes in teat tissue condition. Our secondary objective was to study the association of udder-level milking characteristics and short-term changes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…Our results do not support a measurable relationship between BIM VA , BIM LA , and LDT and STC. The results of the current study contrast with those of a previous study from our group showing an association between udder-level milking characteristics as assessed with electronic on-farm milk meters and STC [40]. Discrepancies in study populations and assessment technique could be variables that account for the differences observed between our previous study and this one.…”
Section: Bimodality Let Down Time and Teat Tissue Conditioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results do not support a measurable relationship between BIM VA , BIM LA , and LDT and STC. The results of the current study contrast with those of a previous study from our group showing an association between udder-level milking characteristics as assessed with electronic on-farm milk meters and STC [40]. Discrepancies in study populations and assessment technique could be variables that account for the differences observed between our previous study and this one.…”
Section: Bimodality Let Down Time and Teat Tissue Conditioncontrasting
confidence: 99%
“…This may have had an influence on our outcome measurements, namely bimodality and STC. However, our results are comparable with those of previous studies investigating bimodality [1,9] or STC [40,44]. We therefore believe that if such an influence had existed, it would have been minor.…”
Section: Study Limitations Practical Application and Future Directionssupporting
confidence: 90%
See 1 more Smart Citation
“…automated scoring system could facilitate exclusion of the nonlactating quarter from evaluation and thereby improve accuracy. Several research groups showed an association between milking characteristics and machine milking-induced changes in teat tissue condition (Nørstebø et al, 2018;Wieland et al, 2018). Linking cow-or quarter-level milk flow data from electronic on-farm milk meters could therefore further improve the accuracy of image-based classification of teat tissue condition.…”
Section: Future Directionsmentioning
confidence: 99%
“…Approaches have included reducing exposure to pathogens by prioritizing improvements to cow housing, ensuring milking hygiene, and minimizing teat lesions (Dodd, 1983;Bartlett et al, 1992). Additional emphasis has been given to milking machine effects and examining the resistance of the teat canal itself to bacterial invasion, considering factors such as overmilking, milk flow, vacuum level, liner slips, and pulsation (Thompson et al, 1978;Natzke et al, 1982;Baxter et al, 1992;Lacy-Hulbert and Hillerton, 1995;Wieland et al, 2018). Research has also focused on the potential dispersal of bacteria in the udder by considering factors such as hand-stripping to remove foremilk and the frequency of udder evacuations (Mein et al, 2004;Shoshani et al, 2017).…”
Section: A Critical Issue For the Dairy Industrymentioning
confidence: 99%